Piperacillin/tazobactam induced toxic epidermal necrolysis and drug induced liver injury - Deep, Hardeep S.; Kumar, Mohit; Singh, Barjinder Pal; Kajla, Nisha (International Journal of Advances in Medicine, 2018)
The liver and skin are the organs most commonly involved in serious adverse drug reactions. Rarely a drug reaction can affect both organs concurrently. The association of drug induced liver injury (DILI) and toxic epidermal necrolysis (TEN) is even rarer and may be rarely reported. This is a case report on development of both TEN and DILI following use of piperacillin / tazobactam. We describe our experience of DILI occurring in association with TEN including the etiological agent responsible, its clinical/ biochemical characteristics and ultimate outcome.